Perencanaan Strategi Reduksi Emisi Gas Rumah Kaca pada Sektor Energi - Putri, Nabila Salma; Budiarti, Eka; Huboyo, Haryono Setiyo; Haryanti, Nurandani (Jurnal Teknologi Riset Terapan, 2024)
Purpose: This study aims to inventory and forecast Greenhouse Gas (GHG) emissions and formulate effective emission reduction strategies in the transportation and industrial sectors of Kendal Regency, with projections extending from 2024 to 2033. Methodology: This study employs Tier 1 and Tier 2 calculation methods based on the IPCC guidelines. Emission projections are modeled under a Business as Usual (BAU) scenario. Mitigation strategies were developed by assessing international best practices and adapting them to the local conditions. Result: By 2033, GHG emissions in the transportation sector are projected to reach 1,596,350 tons of CO? equivalent (CO?eq), while industrial sector emissions are estimated at 111,530.09 tons of CO?eq. The mitigation strategies proposed for the transportation sector could reduce emissions by up to 28%, whereas industrial sector strategies have the potential to cut emissions by up to 76%. Conclusions: Comprehensive mitigation strategies can significantly curb GHG emissions in Kendal Regency. The combination of technological advancements and policy-based interventions offers a robust framework for achieving substantial reductions across both sectors. Limitations: This study is limited by the availability and accuracy of local emission factor data and the assumptions used in BAU projections, which may not fully capture dynamic policy changes or technological breakthroughs. Contribution: This study provides a localized GHG emissions model for Kendal Regency, offering actionable, evidence-based strategies to policymakers and stakeholders to advance regional climate action goals.